2019
DOI: 10.3390/s19061324
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Pilot’s Mental Workload Using ERPs and Spectral Power with a Six-Dry-Electrode EEG System in Real Flight Conditions

Abstract: Recent technological progress has allowed the development of low-cost and highly portable brain sensors such as pre-amplified dry-electrodes to measure cognitive activity out of the laboratory. This technology opens promising perspectives to monitor the “brain at work” in complex real-life situations such as while operating aircraft. However, there is a need to benchmark these sensors in real operational conditions. We therefore designed a scenario in which twenty-two pilots equipped with a six-dry-electrode E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 61 publications
3
83
1
Order By: Relevance
“…On the other hand, humans can handle unexpected events, they have intuition, are creative and capable of making complex (e.g., ethical or moral) decisions. However, the human operator may experience high workload [6] and cognitive fatigue [7,8] that in turn can impair their attentional [9] and executive abilities [10]. In this cybernetic system context, several challenges have arisen such as the implementation of human-robots monitoring autonomously and the volunteers have to supervise the robot's status and manage the water tank supply level.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, humans can handle unexpected events, they have intuition, are creative and capable of making complex (e.g., ethical or moral) decisions. However, the human operator may experience high workload [6] and cognitive fatigue [7,8] that in turn can impair their attentional [9] and executive abilities [10]. In this cybernetic system context, several challenges have arisen such as the implementation of human-robots monitoring autonomously and the volunteers have to supervise the robot's status and manage the water tank supply level.…”
Section: Introductionmentioning
confidence: 99%
“…In the same manner classifiers were trained to detect the cooperation level (always binary) for each subject, and for the team. To do so, a classification pipeline close to that used by Dehais and collaborators [12] and by Roy and collaborators [8] was used. The EEG data processing and classification were run using EEGLab (V14.1.2b) and Matlab (R2019a).…”
Section: Classification Proceduresmentioning
confidence: 99%
“…Using dedicated classification pipelines on various cerebral measures several authors have been able to efficiently estimate an operator's mental workload in laboratory [3], [8], [9] or even in real life settings [10]- [12]. Despite their interest, most of these studies have focused on the monitoring of a single operator.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the nature of the features, there are countless different examples of configurations, in terms of number of channels and frequencies used in the literature. The number of electrodes can vary from 64 [24], [36] to 6 [37], and even the bands considered vary from 2 (Theta and Alpha, [9]), to 7 (0-4 Hz, 4-7 Hz, 7-12 Hz, 12-30 Hz, 30-42 Hz, 42-84 Hz, 84-128 Hz [38]), up to considering all the single frequency bins that define the spectrum [39]. Several studies have shown that it does not necessarily take more than 5-10 electrodes to classify the workload [24].…”
Section: Machine Learning To Get Back Out-of-the-labmentioning
confidence: 99%
“…In fact, if the analysis shows that some electrodes are not useful for the classification of the workload, it is possible to remove them and then make the instrumentation lighter and less invasive. In this case the most used methods for the selection of features are those recursive, such as recursive feature elimination [18], [41], sequential forward feature selection [24] or methods that take into account the dependence between features such as the Minimum Redundancy Maximum Relevance selection [37], [42], [43], or unsupervised method (Locally linear embedding, [44]). Once defined a meaningful set of features, it is necessary to choose a model to define the workload level.…”
Section: Machine Learning To Get Back Out-of-the-labmentioning
confidence: 99%